The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d0me00147c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of charge regulation in oligopeptides

Abstract: Weak ampholytes are ubiquitous in nature and commonly found in artificial pH-responsive systems. However, our limited understanding of their charge regulation and the lack of predictive capabilities hinder the bottom-up...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…Furthermore, the simulated curves in Figure 3 are not only shifted with respect to the ideal curves but also have different slopes, which cannot be described by using pK a eff as the only parameter. These observations are consistent with previous simulation studies on peptides 26,27 and weak ampholytes, 51,52 where it has been shown that this is caused by electrostatic attraction to the oppositely charged groups nearby. Because the pK a values of these acid and base groups differ by more than 3 units, the response of each of them to changes in the pH is characterized by a clearly distinguished inflection point on the dependence of the net charge on the pH (cf.…”
Section: Synthesis Of Poly(2-(imidazol-1-yl)acrylic Acid) (Pimaa)supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the simulated curves in Figure 3 are not only shifted with respect to the ideal curves but also have different slopes, which cannot be described by using pK a eff as the only parameter. These observations are consistent with previous simulation studies on peptides 26,27 and weak ampholytes, 51,52 where it has been shown that this is caused by electrostatic attraction to the oppositely charged groups nearby. Because the pK a values of these acid and base groups differ by more than 3 units, the response of each of them to changes in the pH is characterized by a clearly distinguished inflection point on the dependence of the net charge on the pH (cf.…”
Section: Synthesis Of Poly(2-(imidazol-1-yl)acrylic Acid) (Pimaa)supporting
confidence: 93%
“…40,41 A posteriori, we verified the validity of this assumption by comparing with experimental measurements. Similar coarse-grained models are common in polymer science and have been used in our previous publications to model polyelectrolytes, 42−46 short peptides, 26,27,41 and disordered proteins. 47 The intrinsic pK a values of each acidic and basic group on the monomeric units of the polyzwitterions are the key input parameters of our simulations.…”
Section: Synthesis Of Poly(2-(imidazol-1-yl)acrylic Acid) (Pimaa)mentioning
confidence: 98%
“…In an apparent contradiction with nonideal ionization of weak polyelectrolytes, pH-induced gelation and coacervation seem to be well described by the ideal Henderson–Hasselbalch equation. Experiments and simulation studies of weak polyelectrolytes containing both cationic and anionic groupsblock polyelectrolytes and polyampholytes , have shown that their degree of ionization in dilute solutions substantially differs from the value calculated from eq . In contrast with that, experimental evidence suggests that the Henderson–Hasselbalch equation reasonably describes the ionization of weak polyelectrolytes in coacervate domains.…”
Section: Introductionmentioning
confidence: 91%
“…This last simplification was validated a posteriori by agreement between the trends observed in simulations and in experiments, suggesting that the neglected interactions are not dominant in the studied system. Similar coarse-grained models are ubiquitous in polymer science and have been used in our previous publications to model short peptides , or disordered proteins …”
Section: Materials and Methodsmentioning
confidence: 96%
“…This last simplification was validated a posteriori by agreement between the trends observed in simulations and in experiments, suggesting that the neglected interactions are not dominant in the studied system. Similar coarse-grained models are ubiquitous in polymer science and have been used in our previous publications to model short peptides 28,29 or disordered proteins. 30 The simulation box length was chosen such that one hyperbranched polymer in the simulation box corresponds to c glyc = 1.5 mg/mL, assuming that one bead corresponds to one glucose unit of glycogen.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%